Early-Transmitted Variants and Their Evolution in a HIV-1 Positive Couple: NGS and Phylogenetic Analyses - Lai, Alessia; Giacomet, Vania; Bergna, Annalisa; Zuccotti, Gian Vincenzo; Zehender, Gianguglielmo; Clerici, Mario; Trabattoni, Daria; Fenizia, Claudio (Viruses, 2021)
We had access to both components of a couple who became infected with human immunodeficiency virus (HIV)-1 through sexual behavior during the early initial phase of infection and before initiation of therapy. We analyzed blood samples obtained at the time of diagnosis and after six months of combined antiretroviral therapy. Next-generation sequencing (NGS) and phylogenetic analyses were used to investigate the transmission and evolution of HIV-1 quasispecies. Phylogenetic analyses were conducted using Bayesian inference methods. Both partners were infected with an HIV-1 B subtype. No evidence of viral recombination was observed. The lowest intrapersonal genetic distances were observed at baseline, before initiation of therapy, and in particular in the V1V2 fragment (distances ranging from 0.102 to 0.148). One HIV-1 single variant was concluded to be dominant in all of the HIV-1 regions analyzed, although some minor variants could be observed. The same tree structure was observed both at baseline and after six months of therapy. These are the first extended phylogenetic analyses performed on both members of a therapy-naïve couple within a few weeks of infection, and in which the effect of antiretroviral therapy on viral evolution was analyzed. Understanding which HIV-1 variants are most likely to be transmitted would allow a better understanding of viral evolution, possibly playing a role in vaccine design and prevention strategies.